2017
DOI: 10.1002/2017gl074179
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the influence of atmospheric river orientation and intensity on precipitation distributions over North Coastal California

Abstract: Atmospheric rivers (ARs) are long (>2000 km) and narrow (500–1000 km) corridors of enhanced vertically integrated water vapor and enhanced integrated water vapor transport (IVT) that are responsible for a majority of global poleward moisture transport and can result in extreme orographic precipitation. Observational evidence suggests that ARs within different synoptic‐scale flow regimes may contain different water vapor source regions, orientations, and intensities and may result in different precipitation dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 49 publications
3
51
0
Order By: Relevance
“…However, the apparent modification of the relationship between precipitation and 2-day upslope IVT in varying synoptic conditions motivates an in-depth analysis of the physical mechanisms that generated precipitation in extreme events in subsequent sections. It is worth noting that our isolated focus on extreme events is a fundamental distinction relative to previous studies that showed a strong relationship between IVT direction and precipitation accumulation (e.g., Hecht & Cordeira, 2017). Additionally, the results presented here, based on CFSR and PRISM, cannot be directly compared to previous research that identified a stronger relationship between precipitation and storm-total upslope moisture flux in coastal Northern California using in situ and remotely sensed observations (correlation coefficient of 0.86; Ralph et al, 2013), though the weaker relationship observed in Southern California is consistent with Rutz et al (2014;their Figure 2a).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…However, the apparent modification of the relationship between precipitation and 2-day upslope IVT in varying synoptic conditions motivates an in-depth analysis of the physical mechanisms that generated precipitation in extreme events in subsequent sections. It is worth noting that our isolated focus on extreme events is a fundamental distinction relative to previous studies that showed a strong relationship between IVT direction and precipitation accumulation (e.g., Hecht & Cordeira, 2017). Additionally, the results presented here, based on CFSR and PRISM, cannot be directly compared to previous research that identified a stronger relationship between precipitation and storm-total upslope moisture flux in coastal Northern California using in situ and remotely sensed observations (correlation coefficient of 0.86; Ralph et al, 2013), though the weaker relationship observed in Southern California is consistent with Rutz et al (2014;their Figure 2a).…”
Section: Resultsmentioning
confidence: 91%
“…Regional topography is characterized by transverse (east‐west oriented) coastal ranges, which force orographic precipitation preferentially during landfalling ARs with southerly flow and water vapor transport that is orthogonal to topography (Harris & Carvalho, ). Consequently, the southerly direction of water vapor transport and landfalling AR orientation that are frequently associated with heavy precipitation in Southern California are generated by different synoptic‐scale conditions than those impacting central and northern California (Hecht & Cordeira, ; Oakley & Redmond, ). Heavy precipitation events over Southern California often occur in association with low‐pressure centers that are comparatively closer to the location of AR landfall than those in Northern California (Haynes, ), which increases the likelihood of enhanced mesoscale and synoptic‐scale forcing for precipitation (e.g., convection or quasigeostrophic forcing for ascent, respectively) associated with the parent low‐pressure in addition to orographic precipitation (Small et al, 2002; Oakley et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that the interplay between these circulation features also affects important characteristics of ARs such as landfall orientation, which is important in determining the amount and spatial distribution of precipitation (Ryoo et al, 2013;Hecht & Cordeira, 2017;GSR'17). It is likely that the interplay between these circulation features also affects important characteristics of ARs such as landfall orientation, which is important in determining the amount and spatial distribution of precipitation (Ryoo et al, 2013;Hecht & Cordeira, 2017;GSR'17).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…This variability in frequency and size could be attributed to the different modes of climate variability acting in the region, such as WDs, the Indian monsoon, and low-level jets tied to the terrain and linked with deep convection (e.g., Cannon et al, 2017;Gimeno et al, 2016;Paltan et al, 2017). AR persistence and orientation are functions of the background synoptic-scale flow patterns (e.g., Hecht & Cordeira, 2017).…”
Section: Detection and Characterization Of Ars In Nepalmentioning
confidence: 99%